2009
DOI: 10.1523/jneurosci.5856-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Separate Neural Control of Hand Movements and Contact Forces

Abstract: To manipulate an object, we must simultaneously control the contact forces exerted on the object and the movements of our hand. Two alternative views for manipulation have been proposed: one in which motions and contact forces are represented and controlled by separate neural processes, and one in which motions and forces are controlled jointly, by a single process. To evaluate these alternatives, we designed three tasks in which subjects maintained a specified contact force while their hand was moved by a rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 30 publications
(33 reference statements)
6
55
2
Order By: Relevance
“…The combined results of this and other studies (Chib et al, 2009;Della-Maggiore et al, 2004;Vesia et al, 2010) identify this region as a key area for processing proprioceptive information for motor control. Furthermore, this region can be clearly distinguished from an area around the anterior IPS, which is crucial for online sensorimotor processing in the presence of visual feedback about the hand position.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…The combined results of this and other studies (Chib et al, 2009;Della-Maggiore et al, 2004;Vesia et al, 2010) identify this region as a key area for processing proprioceptive information for motor control. Furthermore, this region can be clearly distinguished from an area around the anterior IPS, which is crucial for online sensorimotor processing in the presence of visual feedback about the hand position.…”
Section: Introductionsupporting
confidence: 67%
“…Studies demonstrating the necessity of the anterior IPS in grasping (Rice et al, 2006Tunik et al, 2005Tunik et al, , 2007 consistently report only changes in the temporal dynamics during the movement, but no spatial effects due to TMS. The studies of Chib et al (2009) and Reichenbach et al (2011) report spatial effects in the order of the effects reported here. The effects of Della-Maggiore et al (2004) seem to accumulate up to 30%.…”
Section: Relevance Of the Observed Tms Effectmentioning
confidence: 88%
See 3 more Smart Citations